Single-Channel Seismic Images from the Western North Atlantic Ocean acquired during R/V Vema expedition V2101 (1965) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Single-Channel Seismic system during R/V Vema expedition V2101 conducted in 1965 (Chief Scientist: Dr. Joseph Worzel). These data files are of JPEG format and include Single-Channel Reflection Seismic images that have not been processed after acquisition.